Generación de conciencia tributaria y su influencia en la recaudación de tributos de las Pymes en el Distrito de los Olivos - Lima - Alayo Cardozo, Carlos Martín (2012)
This research aims to determine the influence of overall generation tax on PYMES tax collection from Los Olivos Town, Lima. Here, it will explore issues such as: the operations done by La Seccion Control y Clausura - SUNAT Intendencia Regional (IR) Lima and the consequences of its application, also it will identify factors that limit voluntary compliance with the obligations of taxpayers and perceptions of them with respect to taxation. To achieve our goal raised the following question: How does the generation of tax awareness in the collection of taxes of PYMES in Los Olivos Town - Lima? For this, we try to prove the following hypothesis: The generation of tax awareness will have positive influence and it will increase tax collection of PYMES in Los Olivos Town - Lima. As study material to test the hypothesis was used as population 13474 PYMES from Los Olivos Town – Lima, as sample was used 374 PYMES and as the unit of analysis was used the person in charge of the management company; and the methods: analytic-synthetic, hypothetical-deductive, inductive-deductive; and techniques were also used as sources of information: Observation, surveys, analysis of administrative documents, making charts and graphs. With this, we have reached the main conclusion, which is, generating adequate tax awareness, increase audits, educating from the beginning to our young generation from schools to understand the importance of a good tax culture and give the right information to all business, will increase the money taxes of PYMES (small and medium business) in Los Olivos Town – Lima.